The Conceptualization of Risk Tolerance and Scale Development for Measuring Publics’ Tolerance of Individual Health Risks (Journal of International Crisis and Risk Communication Research, 2021)
Risk tolerance, identified by scholars over two decades ago as an essential concept in risk communication, has remained understudied without clear conceptual and operational definitions. As the first study developing a multiple-item scale for measuring at-risk publics’ tolerance of different risk types, this study refines the conceptualization of risk tolerance and advances its operationalization in the setting of individual health risks. Qualitative research (in-depth interviews: n = 28; focus group: n = 30) and two survey datasets (sample 1: n = 500; sample 2: n = 500) were employed for scale development and testing. Results identify that two types of individual health risk tolerance exhibited by at-risk publics: (1) Compulsive tendency toward risk taking (CTRT), as evidenced in their unwillingness to refrain from risky behaviors even if they know the negative consequences and (2) inertial resistance to risk prevention (IRRP), as indicated by their indifference toward or intentionally ignoring health messages advocating for behavioral changes. The two-factor 13-item scale’s reliability, factorial structure, and validity are further assessed. This risk tolerance scale provides a valid and reliable psychometric tool for risk communication scholars and practitioners to measure publics’ tolerance of different individual health risks in order to design effective messages to overcome it as a barrier.